2006
DOI: 10.1016/j.cell.2006.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma: Guess Who's Coming to Dinner

Abstract: In this issue of Cell, Coppens and coworkers (Coppens et al., 2006) describe how Toxoplasma gondii, an obligate intracellular parasite, feeds on the host. Coppens et al. provide evidence that the parasite takes host cell endosomes and lysosomes hostage by sequestering them where the parasite resides, within invaginations of the parasitophorous vacuole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…NO production was reported in haemocytes of various bivalve mollusc species (Arumugam et al, 2000;Gourdon et al, 2001;Nakayama and Maruyama, 1998;Ottaviani et al, 1993;Tafalla et al, 2002Tafalla et al, , 2003 and preliminary evidence of ONOO production has been reported in Mytilus galloprovincialis haemocytes (Guerin and Torreilles, 1999) but the NO production in O. edulis had never been measured. Some pathogens can modulate the generation of ROS and RNS (Dermine and Desjardins, 1999;Gruenberg and van der Goot, 2006;Kwok et al, 2005;Müller, 2004;Schott et al, 2003a,b;Volety and Chu, 1995) in order to survive the host defence mechanisms. ROS levels in O. edulis haemocytes after in vitro phagocytosis of B. ostreae were minimal (Cochennec and Garcia, 2000;Hervio, 1992;Morga et al, 2009), which may be due to the block of the respiratory burst by an acid phosphatase activity of the parasite .…”
Section: Introductionmentioning
confidence: 98%
“…NO production was reported in haemocytes of various bivalve mollusc species (Arumugam et al, 2000;Gourdon et al, 2001;Nakayama and Maruyama, 1998;Ottaviani et al, 1993;Tafalla et al, 2002Tafalla et al, , 2003 and preliminary evidence of ONOO production has been reported in Mytilus galloprovincialis haemocytes (Guerin and Torreilles, 1999) but the NO production in O. edulis had never been measured. Some pathogens can modulate the generation of ROS and RNS (Dermine and Desjardins, 1999;Gruenberg and van der Goot, 2006;Kwok et al, 2005;Müller, 2004;Schott et al, 2003a,b;Volety and Chu, 1995) in order to survive the host defence mechanisms. ROS levels in O. edulis haemocytes after in vitro phagocytosis of B. ostreae were minimal (Cochennec and Garcia, 2000;Hervio, 1992;Morga et al, 2009), which may be due to the block of the respiratory burst by an acid phosphatase activity of the parasite .…”
Section: Introductionmentioning
confidence: 98%